Standards and Norms in the English Language. - Locher, Miriam A. (Contributions to the Sociology of Language, v. 95., 2008)
The theme of this collection is a discussion of the notions of 'norms' and 'standards', which are studied from various different angles, but always in relation to the English language. These terms are to be understood in a very wide sense, allowing discussions of topics such as the norms we orient to in social interaction, the benchmark employed in teaching, or the development of English dialects and varieties over time and space and their relation to the standard language. The collection is organized into three parts, each of which covers an important research field for the study of norms and.